Jews with Knives: Toronto's Depression-Era Kosher-Slaughter Infrastructure and the Kehilla Enquiry of 1932. Issue 2 (2nd April 2020) - Ainsworth, Amelia; Halpern, Rick
ABSTRACT: In the 1930s, a legal dispute upset Toronto's kosher-slaughter and kosher-retail industry. The Kehilla, the governing body responsible for regulating the city's kosher system, was accused of charging exorbitant prices for kosher slaughter. Moreover, several community butchers alleged that they had been ostracized from the Municipal Abattoir and coerced into signing binding agreements with a butchers' association. The conflict escalated to such adegree that the city's court mediated the dispute at the request of the Board of Control and City Council. Using foodways as a lens into social and cultural dynamics, this article narrates and examines this kosher controversy to illuminate divisions within the city's Depression-era Jewish community and the larger metropolis. This examination reveals a stratified yet resilient community—one that fostered severe class conflict, but also one that drew on killing-floor activism and an entrepreneurial spirit to secure an economic base in the face of a worsening depression.